2020
DOI: 10.1080/00131881.2020.1780624
|View full text |Cite
|
Sign up to set email alerts
|

Exploring pre-service primary teachers’ progression towards inquiry-based science learning

Abstract: Background: An in-depth understanding of pre-service primary teachers' progression towards teaching science through inquiry is critical for improving teacher education programmes and, ultimately, improving the quality of science teaching and learning in the classroom.Purpose: This study set out to describe and analyse the progression of pre-service primary teachers' learning during an initial teacher education course on how to teach science through inquiry. There was a specific focus on the progression of lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Today's preschoolers are tomorrow's inventors, decision makers, and problem solvers. Therefore, in recent years, concepts such as STEM, robotics, CT, and coding have been promoted by educational institutions and other organizations as skills that are as significantly and equally important for all 21st century students as numeracy and literacy [22,23].…”
Section: Benefits Of Stem Education and Educational Robotics Activitiesmentioning
confidence: 99%
“…Today's preschoolers are tomorrow's inventors, decision makers, and problem solvers. Therefore, in recent years, concepts such as STEM, robotics, CT, and coding have been promoted by educational institutions and other organizations as skills that are as significantly and equally important for all 21st century students as numeracy and literacy [22,23].…”
Section: Benefits Of Stem Education and Educational Robotics Activitiesmentioning
confidence: 99%
“…Knowing that Content Knowledge influences teacher confidence and practices [27] and that lack of CK is particularly common in primary teachers [28], initial teacher education programs for early-level teachers should focus on science topics in which PSTs have difficulties and IBL, to produce considerable progress in their PCK [29]. Indeed, research has shown that primary school teachers are not well prepared to engage their students in inquiry and problem-based learning approaches, which makes it essential to support teachers in developing their PCK [29,30]. Literature on STEM practices and the development of CK and PCK in initial education is scarce, highlighting the lack of investment in this field.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As indicated by [36] (p. 6), science teaching may require "interweaving in a dialectical and complex way, the teacher's moments of knowledge transmission with the student's inquiry moments". Being aware of this, in this work, we consider it desirable that prospective teachers approach constructivist orientations to teach science [3,27]. Understanding the epistemological particularity of students' ideas and the specificity of their didactics is an important tool for prospective teachers to progress in their PCK.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This is a differentiating knowledge that teachers use when planning and teaching, which distinguishes them from other education professionals [1,2]. For science teachers, PCK includes knowledge of students' thinking about science, science curriculum, science-specific instructional strategies, assessment of students' science learning, and orientations to teaching science [3][4][5]. To develop knowledge of pupils thinking about science, an understanding of their initial science ideas and experiences (including misconceptions), the development of science ideas (including process and sequence), how pupils express science ideas (including demonstration of understanding, questions, responses), and the appropriate level of scientific understanding is necessary [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%